KARATERISTIK FISIK KARKAS DAN DAGING RUSA TIMOR (Cervus timmorensis) JANTAN YANG DIPELIHARA DAN HASIL BURUAN PADA JENIS OTOT YANG BERBEDA DI KABUPATEN MERAUKE PAPUA - Dirwan Muchlis (Universitas Musamus, Merauke, Papua, 2012)
The aim of research was to know the meat charateristic and carcass of male deer based on differences of from founded and differences muscle. Reaserch was conducted from April to December 2010 at Animal Health Laboratory Merauke and Laboratory of Animal Product and Technology, Hassanudin University. The research was arangged by Completely Randomized Design (RCD) with factorial pattern (2x3) and three replications. Factor A were from founded male deer and factor B type of muscle (BF Bicep femmoris, ST Semi tendinosus and PP Pectoralis profundus). Parameter measured were value of carccas persentase, pH, Water Holding Capacity (WHC), tenderness, cooking loss and organoleptik test. The result showed percented carccas is not significantly (P<0,05) but muscles type have differences in cooking loss with highest value (36,64%) at semitendinosus type. The interaction between was founded at male deer and muscle types funded in cooking loss and tenderness